Neutrophil-lymphocyte count ratio correlation to procalcitonin and PELOD-2 score in pediatric sepsis - Desak Gede Arie Yudhantari; Dadang Hudaya Somasetia; Eddy Fadlyana; Djatnika Setiabudi (Paediatrica Indonesiana, 2021)
Background Sepsis is a leading cause of children’s mortality worldwide. Procalcitonin (PCT) is a widely used infection marker, but has limitations in terms of cost and availability. The neutrophil-lymphocyte count ratio (NLCR) is easy to perform, low-cost, and widely used as a diagnostic and prognostic marker of various inflammatory processes. Objective To investigate possible correlations of NLCR to PCT and Pediatric Logistic Organ Dysfunction-2 (PELOD-2) score among pediatric sepsis patients. Method A retrospective study was conducted by reviewing the Pediatric Sepsis Registry at Dr. Hasan Sadikin General Hospital, Bandung, West Java, from January 2019–June 2020. We recorded patients’ characteristics, PELOD-2 score, NLCR, and PCT results. Correlation analysis was conducted using Spearman’s Rank test with significance value of P<0.05. Results Ninety patients were included in the study. Most patients were male (56.7%), under 2 years of age (57.8%), and had lower respiratory tract infection (67.8%) as the most common source of infection. The NLCR value had significant, positive correlations to PCT (r=0.642; P<0.001) and PELOD-2 score (r=0.233; P=0.027) in pediatric sepsis patients. Conclusion The NLCR is directly proportional to PCT in pediatric sepsis patients. This result suggents that NLCR may have a potential role as an alternative marker for sepsis in emergency setting.